2007
DOI: 10.1007/s10311-007-0109-y
|View full text |Cite
|
Sign up to set email alerts
|

Visible light-assisted photocatalytic oxidation of organic pollutants using nitrogen-doped titania

Abstract: An experimental research into the aqueous photocatalytic oxidation (PCO) of organic groundwater pollutants, methyl-tert-butyl ether (MTBE), tert-butyl alcohol, phenol, humic substances, 2-ethoxy ethanol and ethylene glycol was undertaken using visible light-sensitive nitrogen-doped titanium dioxide photocatalysts. Nitrogendoped titania proved to be an effective photocatalyst for MTBE with its action comparable to and even surpassing that of Degussa P25. In contrast, with the other substances the photocatalysts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The reason for this inefficiency was found in zero adsorption of lignin on the Ndoped catalysts. The detailed explanation of this observation was given in [31]: the zero adsorption with a good PCO performance with MTBE and TBA indicated the prevailing radical oxidation, ineffective against unadsorbable lignin. In fact, the catalyst synthesized according to [23] did not even form the stable suspensions with lignin solutions like Degussa P25 did.…”
Section: Testing the N-doped Catalystmentioning
confidence: 99%
“…The reason for this inefficiency was found in zero adsorption of lignin on the Ndoped catalysts. The detailed explanation of this observation was given in [31]: the zero adsorption with a good PCO performance with MTBE and TBA indicated the prevailing radical oxidation, ineffective against unadsorbable lignin. In fact, the catalyst synthesized according to [23] did not even form the stable suspensions with lignin solutions like Degussa P25 did.…”
Section: Testing the N-doped Catalystmentioning
confidence: 99%
“…Tert-butyl alcohol (TBA) was chosen as a molecule capable of scavenging free radicals in solution with a low tendency to be absorbed onto titania particles (Klauson et al 2008). The rate constant of free hydroxyl radicals and TBA is in the proximity of 6 9 10 8 M -1 s -1 .…”
Section: Influence Of Free Hydroxyl Radicals Scavengersmentioning
confidence: 99%
“…However, it is active only in the ultraviolet (UV) region because of its wide band gap (3.0-3.2 eV), which accounts for less than 5% of solar energy [3]. Recent studies have revealed that the shortcoming of TiO 2 can be overcome by doping the nonmetal elements such as nitrogen [4][5][6], boron [7], sulfur [8], carbon [9], etc. For example, Asahi et al [4] reported that N-doped TiO 2 showed photocatalytic activity for the decomposition of acetone and methylene blue in wavelengths up to 550 nm because the N 2p states contribute to the band gap narrowing by mixing with O 2p states by substitutional doping of nitrogen.…”
Section: Introductionmentioning
confidence: 99%